An update of Micromyinae (Diptera: Cecidomyiidae) taxonomy, with descriptions of a new genus and 13 new species from Northern Europe - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2020)
While about 100 new species of Micromyinae have been described from Sweden in the past ten years, ongoing research into the country’s fauna continues to unveil previously unknown taxa. This paper provides scientific descriptions of another 13 new species from various parts of Sweden, belonging to six different genera, including a new genus. The new taxa, all to be attributed to both authors, are named as follows: Antennardia suorkensis sp. nov., Aprionus mossbergi sp. nov., Apr. oljonsbynensis sp. nov., Ladopyris baltica gen. et sp. nov. (found also in Estonia), Monardia (M.) lapponica sp. nov., Monardia (Xylopriona) abbreviata sp. nov., Mon. (Xyl.) obscura sp. nov., Neurolyga simillima sp. nov., N. taigensis sp. nov. (found also in the Republic of Karelia, Russian Federation), Peromyia elongatula sp. nov., P. lindstroemi sp. nov. and P. sofielundensis sp. nov. Two new junior synonyms of Aprionus Kieffer, 1894 were identified: Azygotricha Plakidas, 2017 syn. nov. and Ampullomyia Plakidas, 2018 syn. nov., both introduced for Nearctic species. The generic rank of Antennardia Mamaev, previously treated as a subgenus of Monardia Kieffer, is restored. Aprionus internuntius Jaschhof, 2003, previously regarded as synonymous with A. stylifer Mamaev, 1998, is restituted as a valid species. Peromyia assimilis nom. nov. is established as the new substitute name for P. despecta Jaschhof, 2017, found to be a junior homonym of P. despecta Jaschhof, 2010. Micromyinae discovered in Sweden for the first time are Antennardia saxonica Jaschhof, Aprionus heothinos Jaschhof, Apr. internuntius, Monardia (M.) lignivora (Felt), Monardia (Trichopteromyia) relicta Jaschhof, Neurolyga venusta (Mamaev & Rozhnova), Peromyia abdita Jaschhof, and P. brandenburgensis Jaschhof.